Synthesis and Visualization of Entangled 3D Covalent Organic Frameworks with High‐Valency Stereoscopic Molecular Nodes for Gas Separation. Issue 32 (24th June 2022) - Gong, Chengtao; Wang, Hao; Sheng, Guan; Wang, Xiaokang; Xu, Xiaoqiu; Wang, Jian; Miao, Xiaohe; Liu, Yikuan; Zhang, Yinling; Dai, Fangna; Chen, Liangjun; Li, Nanjun; et al.
Abstract: The structural diversity of three‐dimensional (3D) covalent organic frameworks (COFs) are limited as there are only a few choices of building units with multiple symmetrically distributed connection sites. To date, 4 and 6‐connected stereoscopic nodes with T d, D 3h, D 3d and C 3 symmetries have been mostly reported, delivering limited 3D topologies. We propose an efficient approach to expand the 3D COF repertoire by introducing a high‐valency quadrangular prism ( D 4h ) stereoscopic node with a connectivity of eight, based on which two isoreticular 3D imine‐linked COFs can be created. Low‐dose electron microscopy allows the direct visualization of their 2‐fold interpenetrated bcu networks. These 3D COFs are endowed with unique pore architectures and strong molecular binding sites, and exhibit excellent performance in separating C2 H2 /CO2 and C2 H2 /CH4 gas pairs. The introduction of high‐valency stereoscopic nodes would lead to an outburst of new topologies for 3D COFs. Abstract : A new high‐valency quadrangular prism ( D 4h ) stereoscopic molecular node is used to synthesize two isoreticular 3D covalent organic frameworks (COFs). Low‐dose electron microscopy unravels their 2‐fold interpenetrating networks with a bcu topology. The unique pore architectures and strong binding sites enable excellent performance in separating C2 H2 /CO2 and C2 H2 /CH4 gas pairs. The high‐valency molecular node may lead to new 3D COF topologies.